Educators' beliefs towards the teaching of grammar in selected Malaysian private higher learning institutions / Ayuni Madarina Abdul Rahman - Abdul Rahman, Ayuni Madarina (2014)
This study was conducted to investigate educators' beliefs towards grammar teaching in Malaysian Higher Learning Institutions. It specifically highlighted two grammar instructions which are explicit and implicit grammar that have pros and cons in teaching and learning. Due to this, educators are in the midst of dilemma either to teach grammar explicitly or implicitly. Therefore, the researcher would like to see which type of instruction educators believe can be more beneficial to grammar teaching and learning. The specific objectives of the study were to examine educators' beliefs towards grammar teaching, the sources of the held beliefs, the challenges when implementing the beliefs and their coping strategies. The research approach was qualitative in nature and used semi-structured interview. The respondents involved were five educators from various private colleges located in peninsular Malaysia. Findings have shown that a majority of the respondents preferred grammar to be taught explicitly in their ESL classrooms; nevertheless they viewed implicit instruction as necessary also when conforming to students' needs. The sources of the held beliefs are educators' experience as well as the institutional requirement. The results have also shown that there are a few challenges encountered when implementing the held beliefs such as time constraint and varying materials and approaches in teaching, in order to counter the challenges, the educators employed a few coping strategies such as improving their time management and seeking colleagues' collaboration. On the whole, the study shows that both grammar instructions have place in grammar teaching. Hence, educators have to become eclectic teaching practitioners who are able to apply a suitable grammar instruction according to teaching and learning needs. Last but not least, it is hoped this study can contribute to the growthof grammar teaching and learning specifically in ESL classrooms.